The Transmission of Monetary Policy in Israel - De Fiore, Fiorella (IMF Working Papers; Working Paper ;, 1998)
This paper investigates the transmission of Israeli monetary policy since 1990. Two issues are addressed: the extent to which monetary policy exerts real effects, and the relative importance of different transmission channels. The impact of monetary restraints on aggregate industrial production is found to be small, although industrial sectors open to trade appear to suffer to a larger extent than closed sectors. Three transmission channels are analyzed by comparing the empirical evidence to that predicted by theory. While the credit and exchange rate channels may be important mechanisms of transmission, the interest rate channel finds weak support in the data.